Suppression of endoplasmic reticulum stress reverses hindlimb unloading-induced hepatic cellular processes in mice - Ranade, Anu; Khan, Amir Ali; Gul, Muhammad Tehsil; Suresh, Savitha; Qaisar, Rizwan; Ahmad, Firdos; Karim, Asima (Biochimica et biophysica acta. General subjects, 2023)
The Hindlimb unloaded mouse, an animal model of simulated microgravity demonstrates significant metabolic and hepatic derangements. However, cellular and molecular mechanisms driving liver dysfunction in Hindlimb unloaded mice are poorly characterized. We investigated the possible contribution of dysregulated protein homeostasis by endoplasmic reticulum, endoplasmic reticulum stress, to liver dysfunction during HU. C57BL/6j male mice were grouped into ground-based controls or Hindlimb unloaded groups treated daily with vehicle or 4-phenylbutyrate (4-PBA), a potent inhibitor of endoplasmic reticulum stress. Following three weeks of HU, mice were sacrificed, and liver tissues were dissected for further analysis. Hindlimb unloaded was associated with hepatic atrophy and elevated endoplasmic reticulum stress, which was restored by 4-PBA treatment. The Gene Ontology analysis revealed the downregulation of genes primarily involved in liver metabolic and Wingless-related integration site (WNT) signaling pathways, while those related to cytochrome P450, and liver fibrosis were upregulated. The Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed downregulation of several genes involved in metabolic pathways following treatment with 4-PBA, induced by HU. We report several differential and uniquely expressed genes associated with microgravity-induced elevated ER stress and liver injury. Our data has translational potential in unraveling novel molecular targets for pharmaceutical therapies of liver diseases. Our novel findings show a pathogenic role for elevated ER stress in liver injury in microgravity conditions. •Hindlimb unloaded (HU) mouse exhibits features of liver injury.•Liver of HU mice also show elevated endoplasmic reticulum (ER) stress.•Pharmacological inhibition of ER stress in HU mice partially reverses liver injury.•Signature unique transcriptomic changes accompany HU-induced liver injury.•Mitigating ER stress may be a therapeutic target to restore liver during HU.